231 CHRONIC ETHANOL INGESTION CAUSES ALVEOLAR MACROPHAGE DYSFUNCTION: THE ROLE OF PEROXISOME PROLIFERATOR-ACTIVATED RECEPTOR GAMMA. (1st January 2006) - Polikandriotis, J. A.; Gonzalez, F.; Brown, L. A.; Hart, C. M.
Abstract : Rationale: Chronic ethanol (ETOH) ingestion increases the incidence of the acute respiratory distress syndrome (ARDS), a severe form of lung injury with a high mortality rate. Recent studies have clarified numerous alcohol-induced derangements in lung cell function. The current study focuses on the impact of chronic ETOH ingestion on alveolar macrophage function and explores the peroxisome proliferator-activated receptor gamma (PPARg) as a potential therapeutic target in an in vivo rat model of chronic EtOH ingestion. Methods: Male Sprague-Dawley rats were fed liquid diets containing ETOH (36% of calories) or an isocaloric diet substituting maltose-dextrin for ETOH (control) for 6 weeks. After sacrifice, alveolar macrophages were isolated and their ability to phagocytose and internalize fluorescent microorganisms was evaluated using confocal microscopy with and without ex vivo treatment with the PPARg agonist rosiglitazone. In addition, expression of PPARg was examined in isolated macrophages and lung homogenates. Results: Chronic ETOH ingestion in the rat decreased the capacity of alveolar macrophages to bind and internalize infectious particles. In contrast, ex vivo treatment with rosiglitazone restored the phagocytic capacity of the macrophages. Chronic EtOH ingestion also significantly reduced PPARg expression in lung homogenates. Conclusions: These results indicate that chronic EtOH ingestion disrupts macrophage function and reduces PPARg expression in the lung. PPARg agonists such as rosiglitazone may improve the capacity of the alcoholic lung to clear infectious particles and decrease the risk or severity of respiratory infections.